2020
DOI: 10.1037/ocp0000166
|View full text |Cite
|
Sign up to set email alerts
|

Testing a multidimensional model of emotional labor, emotional abilities, and exhaustion: A multilevel, multimethod approach.

Abstract: Addressing health-related risks for employees in the service sector, we identify emotion regulation (ER) ability—a dimension of emotional intelligence—as a promising resource with potential for facilitating emotional labor. We use an event-sampling design to investigate whether person-level ER ability moderates situation-dependent relationships of three different emotional labor strategies with emotional exhaustion in a beneficial way. Study 1 included data from 861 customer interactions from 187 service emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 101 publications
0
12
0
4
Order By: Relevance
“…En la actualidad, la gestión emocional ocupa un lugar central en las organizaciones (Bolton y Boyd, 2003), por ello este campo de análisis ha encontrado en los últimos años un interés creciente entre investigadores y científicos sociales (Grandey, 2000;Grandey et al, 2013;Bolton, 2000;Cheung y Miu-Chi Lun, 2015;Humphrey et al, 2015;Scherer et al, 2020;Seymour y Sandiford, 2005;Totterdell y Holman, 2003;Wharton, 2009;Zapf, 2002). Las transformaciones en el modelo productivo y organizacional desde finales del siglo pasado han ido configurando un escenario en el que la dimensión emocional se ha convertido en un foco clave para entender la cultura organizativa en el sector de servicios.…”
Section: El Trabajo Emocional Como Demanda Emergente En La Sociedad De Serviciosunclassified
“…En la actualidad, la gestión emocional ocupa un lugar central en las organizaciones (Bolton y Boyd, 2003), por ello este campo de análisis ha encontrado en los últimos años un interés creciente entre investigadores y científicos sociales (Grandey, 2000;Grandey et al, 2013;Bolton, 2000;Cheung y Miu-Chi Lun, 2015;Humphrey et al, 2015;Scherer et al, 2020;Seymour y Sandiford, 2005;Totterdell y Holman, 2003;Wharton, 2009;Zapf, 2002). Las transformaciones en el modelo productivo y organizacional desde finales del siglo pasado han ido configurando un escenario en el que la dimensión emocional se ha convertido en un foco clave para entender la cultura organizativa en el sector de servicios.…”
Section: El Trabajo Emocional Como Demanda Emergente En La Sociedad De Serviciosunclassified
“…The study lasted from May 2016 to March 2018. The selection of the research sample was dictated by the fact that interactions with customers are conducted by employees in customer, social or medical services, which also report relatively higher rates of JB (Scherer et al, 2020). Moreover, this group of employees is highly exposed to consumer incivility, which negatively affects their well-being and can lead to JB (Arnold and Walsh, 2015).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Thus, it can be concluded that exhaustion, depersonalisation and a sense of ineffectiveness caused by the state of JB increase the probability of employees ignoring their job duties, performing them unconscientiously or using various forms of deviance in a workplace. This aspect is especially observable in professions that require contacting clients and responding to their needs and problems (Scherer et al, 2020). However, the mechanism is more complex.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of COR theory, if employees need frequent face-to-face interaction, they will feel emotional and physical depletion, a lack of energy, and even extreme tiredness ( Lee and Ok, 2014 ). Therefore, for a surface actor, these emotional regulation demands further burden employees ( Scherer et al, 2020 ; Yeung and Wong, 2020 ). Thus, we echo those findings which demonstrate a strong positive relationship between surface acting and emotional exhaustion in service teams.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%